Sacagawea collection
Correspondence and essays relating to Sacagawea, the Shoshoni woman who served as guide and interpreter for the Lewis and Clark Expedition (1804-1806). Persons represented include Frances Birkhead Beard, Charles H. Burke, Helen M. Crawford, Charles Alexander Eastman, William J. Ghent, David Hilger, John C. Luttig, Nelson A. Mason, and Doane Robinson.
In part, negative photocopy and typewritten transcripts.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Beard, Frances Birkhead; Burke, Charles H; Crawford, Helen M; Eastman, Charles Alexander, -- 1858-1939.; Ghent, William J. -- 1866-1942.; Hilger, David; Luttig, John C., -- -1815.; Mason, Nelson A., -- 1884-1959.; Robinson, Doane, -- 1856-1946.; Sacagawea; Shoshoni women